(untitled) (Journal of Current and Advance Medical Research, 2022)
Background: Placenta praevia is a disorder that happens during pregnancy when the placenta is abnormally placed in the lower uterine segment, which at times covers the cervix. Placenta previa may be associated with placenta accreta (PA) or one of its more advanced forms as (placenta increta and percreta). Objective: The purpose of the present study was to evaluate the maternal and neonatal outcomes in patients with placenta previa and placenta accrete. Methodology: This prospective descriptive study was carried out at Different privet chamber in Dhaka City, during study period from January 2018 to December 2019. Among 75 cases (45 had placenta previa and 30 had placenta accrete) diagnosed preoperatively by ultrasound or postoperatively with or without PA. Maternal and neonatal outcomes were evaluated. All intraoperative and postoperative data were reported. The obtained data was analyzed by means of SPSS software (version 23.0) and p<0.05 was taken as the significant level. Results: Cesarean hysterectomy, Urinary tract injuries, EBL, Patients receiving mean transfusion , mean Operative time, Admission to maternity HDU, Admission to ICU and mean Postoperative hospital stay (days) statistically significant (p<0.05), however age, parity and gestational age was not statistically these were significant (p>0.05) between two groups. IUFD was found 1(3.3%) in placenta accrete group but not found in placenta previa group. Neonatal death was found 1(3.3%) in placenta accrete group but not found in placenta previa group. Conclusion: The incidence of both PP and PA is very high in present locality due to increase CS rate. Admission to maternity HDU, admission to ICU and mean Postoperative hospital stay (days) were significantly difference between women with placenta previa (PP) and placenta accreta (PA). Journal of Current and Advance Medical Research, January 2022;9(1):36-41